Integration of Technology and Character Education in the Teaching Campus 6 Program at GMIM Tonsea Lama Elementary School: Transforming Learning in the Digital Era - Romi Mesra; Preseisilya Selly Palimbong (NALURI EDUKASI JURNAL PENDIDIKAN, 2025)
This study aims to analyze the implementation of technology integration and character education through the Teaching Campus Program at GMIM Tonsea Lama Elementary School and explore its impact on learning transformation in the digital era. The research method uses a qualitative approach with a case study design, with data collection techniques through methodological triangulation including participant observation, documentation, and in-depth interviews. Data analysis was conducted using the Miles and Huberman thematic analysis model with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show significant success in improving students' literacy skills from 52% to 77% and numeracy from 38% to 67% through innovative programs such as "Read Aloud", "3 Vocabulary per Day", and "5 Minutes Playing with Favorite Numbers". The character development program through "Pen Pals", environmental activities, and digital literacy successfully formed empathy, environmental responsibility, and self-confidence in students. Learning transformation occurred through multi-stakeholder collaboration and technological adaptation within limited facilities, creating a sustainable and character-based learning model. This program proves that the integration of technology and character education can be implemented effectively with an adaptive and collaborative approach, making an important contribution to the development of quality education in Indonesia.